A Novel Case of Legionnaire’s Disease after Staying at Home Rentals - Hawayek, Maria Isabel; Aranda, Alvaro; Malpica, Juan (Puerto Rico Health Sciences Journal, 2023)
Case of a 44-year-old woman with past medical history of dermatomyositis who had been on Methrotexate therapy who became infected with Legionella pneumophila after staying at a home rental, known commercially as an Airbnb. The patient presented to the ER with complaints of general malaise and subsequently developed sepsis with respiratory failure requiring intubation. CT scan confirmed the diagnosis of pneumonia and through extensive research L. pneumophila was identified using a pneumonia panel that works by identifying nucleic acids of fastidious organisms that are difficult and take long to grow by culture. As the patient’s pneumonia progressed to ARDS and her clinical impression worsened, pronation technique was begun in addition to her course of antibiotics that were already being administered. The patient began showing significant improvement in her clinical picture and was extubated with progressive recovery.